PENGARUH PERBANDINGAN TEH HITAM (Camellia sinensis) DAN JAHE MERAH (Zingiber officinale var. Rubrum) TERHADAP KARAKTERISTIK TEH CELUP - Savitri, Komang Ayu Melinda; Widarta, I Wayan Rai; Jambe, Anak Agung Gede Ngurah Anom (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 4 (2019): Jurnal ITEPA, 2019)
This study aims to determine the effect of the comparison of black tea and red ginger to the characteristics of teabags and know the comparison of black tea and red ginger to get the best characteristics of tea bags. The experimental design used was Completely Randomized Design with comparison treatment of black tea and red ginger which consist by 6 levels : 100%:0%, 90%:10%, 80%:20%, 70%:30%, 60%:40% and 50%:50%. The treatment was repeated 3 times to obtain 18 units of experiment.. The data obtained were analyzed by variance and if the treatment had significant effect followed by Duncan test. The result showed that tea bags with comaparions of 80% black tea powder and 20% red ginger powder is the best treatments with a water content of 7,78%, extract content of 27,13%, total phenol 247,10 mgGAE/g extract, flavonoids 401,72 mgQE/g extract, antioxidant activity 74,68%, color was liked, distinctive aroma of ginger and rather liked, distinctive taste of ginger and rather liked, overall acceptance was rather like. Keywords : black tea, red ginger, teabag